A High-Precision Machine Learning Algorithm to Classify Left and Right Outflow Tract Ventricular Tachycardia - Zheng, Jianwei; Fu, Guohua; Abudayyeh, Islam; Yacoub, Magdi; Chang, Anthony; Feaster, William W.; Ehwerhemuepha, Louis; El-Askary, Hesham; Du, Xianfeng; He, Bin; Feng, Mingjun; Yu, Yibo; et al. (Frontiers in Physiology, 2021)
Introduction Multiple algorithms based on 12-lead ECG measurements have been proposed to identify right ventricular outflow tract (RVOT) and left ventricular outflow tract (LVOT) locations from which ventricular tachycardia (VT) and frequent premature ventricular complex (PVC) originated. However, a clinical-grade machine learning algorithm that automatically analyzes characteristics of 12-lead ECGs and predicts RVOT or LVOT origins of VT and PVC is not currently available. The effective ablation sites of RVOT and LVOT confirmed by a successful ablation procedure provided evidence to create RVOT and LVOT labels for the machine learning model. Methods We randomly sampled training, validation, and testing datasets from 420 patients that underwent successful catheter ablation (CA) to treat VT or PVC, containing (340, 81%), (38, 9%), and (42, 10%) patients, respectively. We iteratively trained a machine learning algorithm supplied with 1,600,800 features extracted via our proprietary algorithm from 12-lead ECGs of the patients in the training cohort. The area under the curve (AUC) of the receiver operating characteristic (ROC) curve was calculated from the internal validation dataset to choose an optimal discretization cutoff threshold. Results The proposed approach attained the following performance, accuracy (ACC) of 97.62 (87.44 -99.99), weighted F1-score of 98.46 (90-100), AUC of 98.99 (96.89-100), sensitivity (SE) of 96.97 (82.54-99.89), and specificity (SP) of 100 (62.97-100). Conclusions The proposed multi-stage diagnostic scheme attained clinical-grade precision of prediction for LVOT and RVOT locations of VT origin with fewer applicability restrictions than prior studies.